2018
DOI: 10.1007/s10071-018-1208-9
|View full text |Cite
|
Sign up to set email alerts
|

Females in the forefront: time-based intervention effects on impulsive choice and interval timing in female rats

Abstract: Impulsive choice has been implicated in substance abuse, gambling, obesity, and other maladaptive behaviors. Deficits in interval timing may increase impulsive choices, and therefore could serve as an avenue through which suboptimal impulsive choices can be moderated. Temporal interventions have successfully attenuated impulsive choices in male rats, but the efficacy of a temporal intervention has yet to be assessed in female rats. As such, this experiment examined timing and choice behavior in female rats, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
2
9
1
1
Order By: Relevance
“…Posterior distributions for Group and Group × SS Delay effects did not incorporate zero. Thus, the intervention robustly reduced preferences for the immediate reward and sensitivity to delay, consistent with previous studies [31][32][33]39].…”
Section: Model Specificationssupporting
confidence: 88%
See 2 more Smart Citations
“…Posterior distributions for Group and Group × SS Delay effects did not incorporate zero. Thus, the intervention robustly reduced preferences for the immediate reward and sensitivity to delay, consistent with previous studies [31][32][33]39].…”
Section: Model Specificationssupporting
confidence: 88%
“…Categorical variables (group and sex) were effects coded so that all tests were conducted relative to the grand mean of the data. SS delay was coded as a continuous variable and scaled with two different intercepts: 0-s and 30-s delays [31,39,53]. The 0-s delay intercept predicted choices at a 0-s SS delay to assess the intervention effects on bias for immediacy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VI intervention did not improve timing at a group level (i.e., the rats in the VI intervention group did not generally perform better than the rats in the control group), but individual rats that made more self-controlled choices postintervention also showed greater timing precision in a temporal bisection task, which is used to measure discrimination of time intervals. Stuebing et al (2018) extended the FI time-based intervention to female rats and reported that the intervention improved self-controlled choices compared to a no-delay control group. However, the female rats did not show improved timing precision in a temporal bisection task.…”
Section: Timing Interventions and Impulsive Choicementioning
confidence: 99%
“…Parameters in Experiment 2 produced decreasing hazard functions that were not overly steep or shallow. Very steep functions would have resulted in near‐exclusive delivery of immediate reinforcers, which do not consistently affect self‐control (Fox et al, 2019; Peterson & Kirkpatrick, 2016; Renda et al, 2018; Stuebing et al, 2018). A shallower HFD function would have closely approximated HF0, which did not improve self‐control in Experiment 1.…”
Section: Discussionmentioning
confidence: 99%